IMPLEMENTASI PAPAN INFORMASI DIGITAL MENGGUNAKAN RASPBERRY PI 3 PADA STIPER SRIWIGAMA PALEMBANG - Dasmen, Rahmat Novrianda; Halim, Nasrul (Computatio : Journal of Computer Science and Information Systems, 2018)
STIPER Sriwigama Palembang is one of the high school agricultural sciences located in the city of Palembang. As with other universities, in the STIPER Sriwigama Palembang environment there are lecturers, staff and students. STIPER Sriwigama Palembang in informing about the presence of lecturers is currently still using a simple manual information board to display the names of lecturers present or not with a static, unattractive and inaccurate display. The purpose of this research is to build a dynamic digital information board where information in it can be arranged according to needs, which can be managed by the information section. This research uses Raspberry Pi which will connect the LED TV with the computer part information. This research will produce an information board that contains interesting features such as the use of running images and text and provide information about the presence of lecturers who are teaching or not teaching which can be arranged through the computer information section. Because it is still in the research process, the current output will be explained limited to the display design and also explained about the configuration of the Raspberry Pi 3 model B so that it can modify the LED TV into a digital information board.